Optimalisasi Penyaluran Bantuan Program Keluarga Harapan Menggunakan Metode Fuzzy SAW pada Sistem Pendukung Keputusan - Nita Syahputri; Fithry Tahel; Elida Tuti Siregar; Erwin Ginting (Journal of Information System Research (JOSH), 2025)
This study aims to design and implement a decision support system (DSS) used on the Fuzzy Simple Additive Weighting (Fuzzy SAW) method to improve the accuracy and objectivity of the selection process for recipients of the Family Hope Program (PKH) in Hamparan Perak Village. The system was developed to address the limitations of manual selection, which remains subjective and inefficient. The research involved several stages, including needs analysis, system design using Unified Modeling Language (UML), and testing through the black-box method. The system utilizes social criteria data such as housing conditions, number of dependents, and informal employment status, which are processed using a fuzzy approach to produce structured recommendations. The main innovation of this system lies in the integration of localized indicators and a mobile-based data update module, enabling real-time verification and validation in the field. The implementation results indicate that the system operates optimally and can be utilized by village officials with limited digital literacy. This research contributes to strengthening data-driven governance in social assistance distribution and has the potential to be replicated in other regions with similar socio-demographic characteristics.